2015
DOI: 10.1098/rsob.140218
|View full text |Cite
|
Sign up to set email alerts
|

A species-specific nucleosomal signature defines a periodic distribution of amino acids in proteins

Abstract: Nucleosomes are the basic structural units of chromatin. Most of the yeast genome is organized in a pattern of positioned nucleosomes that is stably maintained under a wide range of physiological conditions. In this work, we have searched for sequence determinants associated with positioned nucleosomes in four species of fission and budding yeasts. We show that mononucleosomal DNA follows a highly structured base composition pattern, which differs among species despite the high degree of histone conservation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 46 publications
(61 reference statements)
2
19
0
4
Order By: Relevance
“…These differences are consistent with the phylogenetic distance of 119, 221, and 350 million years of S. octosporus, S. japonicus and S. cerevisiae, respectively, relative to S. pombe Hoffman et al 2015) and with the fact that the nucleosomal signatures are more similar between S. octosporus and S. pombe than between S. japonicus and S. pombe ( Fig. 5; Quintales et al 2015a). It is currently unknown whether these small differences in the histone octamer could be responsible for the different affinity of nucleosomes of different organisms for the same DNA sequence or whether other factors like histone concentration, the linker-tocore histone ratio, or other thermodynamic or biophysical parameters could be involved (Beshnova et al 2014).…”
Section: Wwwgenomeorgsupporting
confidence: 75%
See 4 more Smart Citations
“…These differences are consistent with the phylogenetic distance of 119, 221, and 350 million years of S. octosporus, S. japonicus and S. cerevisiae, respectively, relative to S. pombe Hoffman et al 2015) and with the fact that the nucleosomal signatures are more similar between S. octosporus and S. pombe than between S. japonicus and S. pombe ( Fig. 5; Quintales et al 2015a). It is currently unknown whether these small differences in the histone octamer could be responsible for the different affinity of nucleosomes of different organisms for the same DNA sequence or whether other factors like histone concentration, the linker-tocore histone ratio, or other thermodynamic or biophysical parameters could be involved (Beshnova et al 2014).…”
Section: Wwwgenomeorgsupporting
confidence: 75%
“…6D, dotted trace) confirmed this result and showed that, in some cases, internucleosomal positions in S. cerevisiae coincided with dyad positions in S. pombe. This could be due to the fact that A + T-rich sequences are preferentially found at the dyad and linker regions in S. pombe and S. cerevisiae, respectively (Tillo and Hughes 2009;Moyle-Heyrman et al 2013;Quintales et al 2015a). …”
Section: Engineering Nucleosomal Positioning On Synthetic Noncoding Dmentioning
confidence: 99%
See 3 more Smart Citations